From agricultural waste to active films: Enhanced crystallinity of spent mushroom substrate-derived cellulose via deep eutectic solvent-based microwave-assisted pretreatment and its application in reinforcing CMC-based composite films - Antira Wichaphian; Phonthida Yasan; Wasu Pathom-aree; Saisamorn Lumyong; Nakarin Suwannarach; Jaturong Kumla; Supakit Chaipoot; Supawitch Hoijang; Tharnthip Krasian; Patnarin Worajittiphon; Winita Punyodom; Benjamas Cheirsilp; et al. (Journal of Agriculture and Food Research)
This study demonstrates the successful valorization of spent mushroom substrate (SMS), an abundant agricultural waste, into crystalline cellulose for advanced food packaging applications. A deep eutectic solvent (DES)-based microwave-assisted pretreatment was developed to extract and enhance cellulose crystallinity from SMS. Using optimized conditions—choline chloride and zinc acetate DES at 1:1 M ratio, 1:30 w/v cellulose-to-DES ratio, 640 W microwave power, and 2.5-min hydrolysis—the process yielded pretreated cellulose (PC) with 51.66 % crystallinity index and 95.82 % recovery yield. The PC was then incorporated into carboxymethyl cellulose (CMC)-based composite films along with zinc oxide nanoparticles (ZnONPs) and mushroom powder (MP). The resulting composite films exhibited superior mechanical properties, with CMC/PC/ZnONPs films achieving a tensile strength of 17.18 MPa and toughness of 4.72 MJ/m3. Integration of ZnONPs and MP enhanced UV-blocking capabilities while maintaining film transparency. The films demonstrated thermal stability with melting temperatures ranging from 257.5 °C to 281.83 °C. Notably, PC-containing films showed improved antioxidant activity, with IC50 values of 4.59–8.57 mg/mL for 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) and 134.88–1389.15 mg/mL for 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. The composite films also exhibited strong antimicrobial properties against common foodborne pathogens (Staphylococcus aureus, Escherichia coli, and Bacillus subtilis), with inhibition zones exceeding 15 mm. This research establishes a sustainable approach to waste valorization while advancing the development of multifunctional, eco-friendly food packaging materials.